Preparation, preliminary pharmacokinetics and brain tissue distribution of Tanshinone IIA and Tetramethylpyrazine composite nanoemulsions. (26th November 2019) - Wang, Beilei; Hong, Lufeng; Liu, Yuanxu; Bedingfield, Sean K.; Zhang, Caiyun; Peng, Can; Qian, Jiajia; Zha, Liqiong
Abstract: Objective: Tanshinone IIA (TSN) and Tetramethylpyrazine (TMP) were combined in a composite, oil-in-water nanoemulsions (TSN/TMP O/W NEs) was prepared to prolong in vitro and vivo circulation time, and enhance the bioavailability of TSN. Material and methods: Physicochemical characterization of TSN/TMP O/W NEs was characterized systematically. The in vitro dissolution and in vivo pharmacokinetic experiments of TSN/TMP O/W NEs were also evaluated. Result: A formulation was optimized, yielding a 32.5 nm average particle size, an encapsulation efficiency of over 95 %, and were spherical in shape as shown by TEM. TSN/TMP O/W NEs were shown to extend the release and availability in vitro compared to raw compounds. In pharmacokinetic study, the AUC0→∞ and t 1/2 of the TSN/TMP O/W NEs were 481.50 mg/L*min and 346.39 min higher than TSN solution, respectively. Brain tissue concentration of TSN was enhanced with TSN/TMP O/W NEs over raw TSN and even TSN O/W NEs. Conclusions: Therefore, nanoemulsions are an effective carrier to increase encapsulation efficiency of drugs, improve bioavailability and brain penetration for TSN – which is further enhanced by pairing with the co-delivery of TMP, providing a promising drug delivery. Abstract :